Crystallography of modular materials - Ferraris, Giovanni; Makovicky, E.; Merlino, Stefano; International Union of Crystallography (Oxford : Oxford University Press, 2004)
This comprehensive text is addressed at scientists who are interested in considering crystalline materials from a non-conventional but inspiring viewpoint. It contains the first systematic theoretical and illustrative presentation of crystalline materials built from modules.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular crystals -- Structure; Twinning (Crystallography)